Freeze-Thaw Durability Evaluation of Quarried Limestone Coarse Aggregates for Transportation Infrastructure Applications - (:unkn) unknown (My University, 2022)
Aggregates are an important component of transportation infrastructure used as unbound base material and within Portland cement concrete (PCC) structures. In cold climate regions, seasonal freeze and thaw cycles cause damage to aggregate and impact pavements, bridges, and other transportation infrastructure performance. This research investigated Wisconsin quarried coarse aggregates for freeze-thaw durability as unbound aggregates as well as in PCC mixtures for pavement surface. A comprehensive laboratory testing program was conducted on 21 coarse aggregate samples consisting of calcareous and dolomitic limestone including sodium sulfate soundness, freeze-thaw testing, and absorption. Furthermore, three sources of these coarse aggregates were used to prepare concrete mixes, according to WisDOT mixture design for PCC pavements, and cast PCC cylinders for stiffness and strength evaluation due to rapid freeze-thaw conditioning. Results of the testing program demonstrated variable results for the investigated coarse aggregates in which poor correlation was exhibited between sodium sulfate soundness and freeze-thaw soundness testing on unbound aggregates. Variation in the mass loss values from freeze-thaw testing and sodium sulfate soundness testing for calcareous versus dolomitic limestone coarse aggregates suggests different mechanisms of aggregate degradation occur between the test methods. Testing on PCC cylinders with the investigated coarse aggregates showed that the aggregate does not appear to have a significant impact on the rapid freeze-thaw degradation of concrete when a high-quality mixture and high entrained air content is utilized. Another reason could be that the applied number of freeze-thaw cycles did not result in a tangible aggregate damage within the PCC to significantly influence the PCC strength and stiffness.